New Trade Theory and Aggregate Export Equations: an Application of Panel Cointegration. - Driver, R; Wren-Lewis, S (School of Business and Economics (University of Exeter), 1999)
New trade theory suggests that improvements in the variety and quality of products may be as important as price competitiveness as an explanation of trade flows. This paper tests this proposition for export volumes for the G7 using relative cumulated investment as a proxy for innovation. Positive results are obtained using new panel cointegration techniques as well as more traditional methodologies.